Microalgae Growth in a Biocathode-Photosynthesis Microbial Desalination Cell: Molecular Characterization, Modeling Study, and Performance Evaluation - Sadeq, Ahmed M.; Ismail, Zainab Z. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
This study aimed to comprehensively characterize and identify microalgae inhabiting the biocathode compartment of a photosynthetic microbial desalination cell (PMDC). Also, modeling of microalgae growth in the biocathode was considered as well as the interrelation between the growth of microalgae and dissolved oxygen (DO) generation within the biocathode. The general performance of the PMDC was evaluated based on; (1) organic content removal from the real domestic wastewater fed to the anode compartment, (2) salinity removal from actual seawater in the desalination compartment, and (3) power generation in the PMDC. The results unveiled the presence of two distinct microalgae species, specifically Coelastrella sp. and Mariniradius saccharolyticus, which were thoroughly characterized using 16S rRNA and ITS gene sequencing within the cathodic chamber of the PMDC. Following sequence editing and trimming, the resulting sequences were meticulously submitted to the NCBI GenBank and juxtaposed with other sequences utilizing the GenBank online BLAST software. Importantly, the obtained data demonstrated a good correlation with coefficients of determination (R²) reaching 0.83, as per the employed kinetic models. Complete removal of up to 99.11% of organic content from the real domestic wastewater was obtained in the PMDC system with maximum efficiency of desalination elimination of 80.95% associated with a maximum power output of 420 mW/m3 in the system.